THE INFLUENCES OF LIVE STREAMING AND FLASH SALE IN TIKTOK SHOP TOWARD PURCHASE DECISION OF ECONOMICS AND BUSINESS FACULTY, SAM RATULANGI UNIVERSITY STUDENTS - Oroh, Dhea Gloria Chrisvynia; Tumbuan, Willem J. F. A; Gunawan, Emilia M. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
Purchase decision is an important thing for a company, it plays a big role in sales. The aim of this study is to find out the influences of live streaming and flash sale in Tikok shop toward purchase decision of students in Faculty of Economics and Business, Sam Ratulangi University. The sample of this research is using 100 respondents and using purposive sampling for the sampling technique. The respondents are active students of Economics and Business Faculty, Sam Ratulangi University and students who use TikTok. The result shows that Live Streaming and Flash Sale positively influence purchase decision of students of Economics and Business Faculty, Sam Ratulangi University. In this study, the existence of live streaming and flash sale that offer opportunity for customer to get products information easier and the lesser price that have been provided by live streaming and flash sale in TikTok shop can lead to purchase decision of Economics and Business Faculty, Sam Ratulangi University students due to the lack of income that they have.   Keywords: Live Streaming, Flash Sale, Purchase Decision